MATERNAL CHARACTERISCTICS OF LOW BIRTH WEIGHT WITH KANGAROO MOTHER CARE AND PLASTIC WRAP - Yulida Mufidah; Dominicus Husada; Esti Yunitasari; Risa Etika (Indonesian Midwifery and Health Sciences Journal, 2020)
AbstractBackground: Most Infant mortality due to low weight birth (42%). The babies need care to reduce mortality/morbidity such us Kangaroo methode and Plastic Wrap. Both of these methods aim to prevent hypothermia. This research to describes implementation of the Kangaroo Method and Plastic Wrap including input (mother, father and baby), process (staff and duration of care) and outcomes (hypothermia and Lenght of Stay). Method: Descriptive-Cross Sectional with number of sample of low birth weight are 96 (Kangaroo) and 98  babies (Plastic Wrap). The variables research are maternal age, parity, education, risk factor, complications and National health insurance’s participant. The instrument used medical records. Data analysis with frequency distribution. Result: Maternal age majority in Kangaroo Method and Plastic Wrap 20-35 years old (77,08% and 70,41%), multiparity (57,30% and 60,2%), Middle education (43,75% and 60,20%),high risk (71,87% and 55,10%), Preeclampsia (33,33% and 43,88%), Health Insuranse’s participant (79,17% and 63,27). Conclusion: data shows input, process and output of KMC and Plastic Wrap.